2019
DOI: 10.1161/jaha.119.012530
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Ticagrelor in Comparison to Clopidogrel in Elderly Patients With ST‐Segment–Elevation Myocardial Infarctions

Abstract: BackgroundCurrent guidelines recommend the new‐generation P2Y12‐inhibitor ticagrelor for patients with acute ST‐segment–elevation myocardial infarctions (STEMIs). The aim of the present study was to assess efficacy and safety of ticagrelor for elderly patients with STEMI (≥75 years) in an all‐comers STEMI registry.Methods and ResultsPatients with STEMI, aged ≥75 years, treated with primary percutaneous coronary intervention and documented in the Bremen STEMI Registry between 2006 and 2017 entered analysis. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 23 publications
1
22
1
Order By: Relevance
“…Additionally, there is evidence that potent P2Y 12 inhibition may offer benefits in patients with T2DM and complications such as lower extremity arterial disease, in which ticagrelor improves microvascular flow, for example [45]. Although there has been concern over greater bleeding risk increasing the potency of P2Y 12 inhibition, recent evidence suggests, for example, ticagrelor may have similar safety to clopidogrel in patients at high risk of bleeding, such as those who are elderly with ST-elevation myocardial infarction [46], and low-dose prasugrel appears to be of comparable safety to clopidogrel when used in triple therapy (aspirin, P2Y 12 inhibitor and anticoagulant) for patients with atrial fibrillation undergoing percutaneous coronary intervention [47].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is evidence that potent P2Y 12 inhibition may offer benefits in patients with T2DM and complications such as lower extremity arterial disease, in which ticagrelor improves microvascular flow, for example [45]. Although there has been concern over greater bleeding risk increasing the potency of P2Y 12 inhibition, recent evidence suggests, for example, ticagrelor may have similar safety to clopidogrel in patients at high risk of bleeding, such as those who are elderly with ST-elevation myocardial infarction [46], and low-dose prasugrel appears to be of comparable safety to clopidogrel when used in triple therapy (aspirin, P2Y 12 inhibitor and anticoagulant) for patients with atrial fibrillation undergoing percutaneous coronary intervention [47].…”
Section: Discussionmentioning
confidence: 99%
“…Ticagrelor, a “next generation” P2Y12 receptor inhibitor is an alternative antiplatelet therapy commonly prescribed to patients with CAD. It has demonstrated its efficacy as an antiplatelet medication when compared with ASA and clopidogrel [ 20 , 43 ]. The THEMIS trial conducted by Steg et al in 2019 demonstrated that patients with stable CAD and diabetes benefited from taking ticagrelor in combination with ASA, compared to ASA and a placebo [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ticagrelor is an alternative antiplatelet therapy that is commonly prescribed to patients with acute coronary syndrome (ACS), defined as patients with unstable angina, non-ST-segment elevation myocardial infarctions (NSTEMI), or ST-segment elevation myocardial infarctions (STEMI), as well as patients with a previous history of myocardial infarction (MI) [ 19 , 20 , 21 ]. This medication binds to, and reversibly inhibits the P2Y12 adenosine diphosphate (ADP) receptor on platelets, inhibiting ADP-induced platelet aggregation [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, as previously described [23,[26][27][28], we have confirmed that in clinical practice, the baseline characteristics of patients taking clopidogrel-DAPT are significantly different from those in treatment with new antiplatelet-DAPT. In European registries [23], patients treated with prasugrel are usually younger than those treated with ticagrelor [31], and patients treated with clopidogrel are older, with almost 10 years of difference in some studies. Danchin et al [23] showed that older age is usually associated with more comorbidities and higher cardiovascular risk, as we confirm in our study.…”
Section: Discussionmentioning
confidence: 99%